Single-phase coronary artery CT angiography extracted from stress dynamic myocardial CT perfusion on third-generation dual-source CT: Validation by coronary angiography. (15th October 2018) - Yi, Yan; Wu, Wei; Lin, Lu; Zhang, Hong-Zhi; Qian, Hao; Shen, Zhu-Jun; Wang, Yun; Jin, Zheng-Yu; Litt, Harold; Wang, Yi-Ning
Abstract: Background: CT advances allow coronary arterial tree to be entirely covered during one CTP scan. Our aim was to investigate the potential value of single-phase coronary CT angiography (SP-CCTA) extracted from stress dynamic myocardial CT perfusion (CTP) for coronary artery stenosis assessment. Methods: Consecutive symptomatic patients were prospectively recruited and scanned with an ATP-stress dynamic myocardial CTP and routine CCTA protocol using third-generation DSCT. Noise reduction was applied to optimize image quality (IQ), the CTP phase with the best enhancement of the coronary arteries was selected as the SP-CCTA. IQ was assessed qualitatively. Using coronary angiography (CAG) as the reference standard, the diagnostic performance for stenosis detection was compared for SP-CCTA and routine CCTA. Results: 56 patients underwent the CTP and CCTA examination, among which 39 patients underwent CAG. The qualitative IQ scores of SP-CCTA were similar to that of routine CCTA (p > 0.05). On a per-segment basis, the sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy and area under the receiver-operating-characteristic curve results of SP-CCTA and routine CCTA for diagnosis of stenosis ≥50% exhibited no significant difference (SP-CCTA: 78.1%, 94.9%, 77.4%, 95.1%, 91.6% and 0.935 vs. routine CCTA: 74.7%, 95.3%, 78.0%, 95.3%, 91.6% and 0.937; all p > 0.05). The mean effective radiation dose of CTP and routine CCTA plus CTP were 3.92 ± 1.72 mSv and 5.98 ± 2.01 mSv (p < 0.05), respectively. Conclusions: The IQ and diagnostic value of SP-CCTA was equivalent to routine CCTA on third-generation DSCT. SP-CCTA images from CTP may potentially replace a separate routine CCTA, allowing the possibility of "one-stop" cardiac examination for high-risk CAD patients who need myocardial ischemia assessment. Highlights: The first study of SP-CCTA images extracted stress dynamic myocardial CTP. SP-CCTA images is potentially feasible to replace a separate routine CCTA acquisition. SP-CCTA is promisingly streamlining the clinical process into a low dose "one-stop" cardiac CT.